Jejuno-Jejunal Intussusception in an Adult Creole Horse - Tassoni Andriotti, Bárbara; Pioner de Jesus, Bruna; Dall’Agnol Krause, Catherine; Paiva Del Manto, Jade; dos Santos Meirelles, Guilherme; Maciel Fernandes, Louise; Mondardo Cardoso, Henrique; Carolina Barreto Coelho, Ana (Acta Scientiae Veterinariae, 2025)
Background: Colic syndrome is a leading cause of death in horses. Anatomical peculiarities predispose horses to morphophysiological changes. Intussusception, an important cause of colic in foals, is uncommon in adult horses. It is characterized by the invagination of an intestinal segment into an adjacent aboral segment. Small intestinal intussusception is believed to develop because of abnormal intestinal peristalsis, causing acute and progressive abdominal discomfort. Herein, we aimed to report a rare case of intussusception of the jejuno-jejunal portion of the small intestine in a 10-year-old Criollo horse. Case: A 10-year-old Crioulo horse, weighing 400 kg, was referred to the veterinary hospital with acute colic syndrome. On the property, the horse demonstrated signs of being in intense pain. A sudden feed change without a gradual transition was reported. The horse was treated with nonsteroidal anti-inflammatory drugs to relieve the pain, and a nasogastric tube was inserted. However, he continued to demonstrate signs of being in severe pain, and his condition was not stable. Therefore, he was referred to the hospital for further management. Upon arrival, a blood test was performed, which revealed a hematocrit below the reference value and a leukogram with numerous platelet clusters. On physical examination, the horse’s heart rate, respiratory rate, and rectal temperature were within normal limits, and the mucous membranes were pale. Transabdominal ultrasound revealed thick walls in the small intestinal segment and overlapping loops. To confirm the diagnosis, an exploratory laparotomy was performed with the horse in a dorsal decubitus position and under inhalation anesthesia. On inspection, the loops of the small intestine were congested and distended, and the intussusception was identified in the middle-to-distal 3rd of the jejunum. The origin of the invagination was located, and the intussusceptum was separated from the intussuscipien. Because of the injuries caused to the mucosa by strangulation, the affected intestinal portion was excised using the technique of intestinal wall reduction, resection, and anastomosis. The colon was washed and repositioned, and celiorrhaphy was performed on the 3rd postoperative day, an abdominal ultrasound was performed. It demonstrated normal intestinal flow, indicating that the surgical intervention had effectively corrected the condition and restored intestinal function. Discussion: The diagnosis of intussusception was established on the basis of clinical signs, ultrasound findings, and macroscopic changes observed during a laparotomy. Jejunal intussusception is uncommon in adult horses, and it is more prevalent in young animals aged 6 months to 3 years. Although intussusception is uncommon in adult animals, its incidence in this age group cannot be underestimated because it can cause serious pathologies, requiring immediate diagnosis and surgical intervention to avoid irreversible damage. Abrupt changes in the diet may be an important predisposing factor, regardless of the animal’s age. Ultrasonography is a good diagnostic tool for intussusception, which appears as a characteristic “target lesion” or “bull’s eye.” Exploratory laparotomy is the most appropriate treatment choice, allowing confirmation of the diagnosis of intussusception and effective resolution of the symptoms. Keywords: equine colic, exploratory laparotomy, ultrasonography. Título: Intussuscepção jejuno-jejunal em cavalo adulto da raça Crioula Descritores: laparotomia exploratória, síndrome cólica equina, ultrassonografia.